Changes in magnetic resonance bone marrow angiogenesis on day 7 after induction chemotherapy can predict outcome of acute myeloid leukemia - Hou, Hsin-An (Ferrata Storti Foundation, 2010)
Recently, dynamic contrast-enhanced magnetic resonance imaging has been shown to be a non-invasive technique that provides global and functional imaging of bone marrow angiogenesis in acute myeloid leukemia. To assess the clinical implication of changes in angiogenesis shortly after induction chemotherapy, dynamic contrast-enhanced magnetic resonance imaging was performed prospectively before treatment (day 0) and on day 7 in 80 patients with de novo acute myeloid leukemia. We demonstrated that a post-therapeutic reduction in Peak (negative ΔPeak) compared with the day 0 value was significantly associated with a higher chance of achieving complete remission, and better overall and disease free survival (P=0.022, 0.003 and 0.007, respectively). Cox’s multivariate analysis also identified negative ΔPeak value as an independent good prognostic factor for overall and disease free survival. Our findings provide evidence that the change of Peak on day 7 relative to pre-treatment levels may be a relevant biomarker for early identification of patients who may fail conventional induction chemotherapy (ClinicalTrials.gov Identifier: NCT00172562).